Book Review - Ventura, Sylvia Mendez (Review of Women's Studies, 1990)
Book review of Sarilaya: Women in Arts and Media. Edited by Sr. Mary John Mananzan, OSB, Ma. Asuncion Azcuna, and Fe Mangahas. The Institute of Women's Studies. St. Scholastica's College, Manila, 1989.